Diffusion‐weighted MRI treatment monitoring of primary hypofractionated proton and carbon ion prostate cancer irradiation using raster scan technique. Issue 3 (2nd February 2017) - Wolf, Maya B.; Edler, Christopher; Tichy, Diana; Röthke, Matthias C.; Schlemmer, Heinz‐Peter; Herfarth, Klaus; Bonekamp, David
Abstract : Purpose: To investigate parametric changes in the apparent diffusion coefficient (ADC) at multiple timepoints during and after completion of primary proton and carbon ion irradiation of prostate cancer (PCa) as compared with normal‐appearing prostate parenchyma. Materials and Methods: In all, 92 patients with histologically confirmed PCa received either proton or carbon ion hypofractionated radiotherapy (RT). All were prospectively evaluated with diffusion‐weighted magnetic resonance imaging (DWI‐MRI) at five timepoints: baseline, day 10 during therapy and 6 weeks, 6 months, and 18 months after treatment. Linear mixed models (LMM) were used to evaluate the effects of radiation, antihormonal therapy, time, and type of particle irradiation on manual ADC measurements. ADC differences related to prostate‐specific antigen (PSA) relapse according to PSA thresholds and to Vancouver rules and Phoenix criteria were examined using LMM and unpaired Student's t ‐test. Results: A measurable and continuous increase of tumor ADC measurements from baseline (1.194 × 10 −3 mm 2 /s) during (1.350 × 10 −3 mm 2 /s, day 10, P  = 0.006) and after treatment (1.355/1.430/1.490 × 10 −3 mm 2 /s, week 6 / month 6 / month 18, P  = 0.001/<0.001/<0.001) was found. ADC values of normal‐appearing control tissue remained unchanged. Androgen deprivation ( P  ≥ 0.320), different PSA thresholds ( P  = 0.634), and PSA relapse criteria according to Vancouver rules ( P ≥ 0.776) had no effect. A weak association between 18‐month measurements and Phoenix criteria ( P  = 0.046) was found. Conclusion: ADC parametric changes were distinct in tumor tissue, highlighting the ability of diffusion MRI to evaluate different aspects of the microscopic pathophysiology. Although promising, their use as noninvasive imaging biomarkers requires further validation. Level of Evidence: 1 Technical Efficacy: Stage 1 J. MAGN. RESON. IMAGING 2017;46:850–860